No‐tillage effects on soil properties under different crops in Western Nigeria - Lal, R. (1976)
Five years of no-tillage vs. the conventional method of tractor plowing significantly affected the physical and chemical properties of an Alfisol in western Nigeria. Continuous cropping of maize for 3 consecutive years was followed by 4 seasons of cultivation with cropping sequences of maize-maize (Zea mays L.), maize-cowpeas (Vigna unguiculata L. walp.), pigeon peas (Cajanus cajan Millsp.)-maize, soybeans-soybeans (Glycine max Merr.), maize-soybeans, and cowpeas-cowpeas. The no-tillage plots had higher organic matter contents in the surface soil horizons and higher concentrations of nitrate-nitrogen, Bray-1 available phosphorus, and ammonium acetate extractable cations such as Ca2+, Mg2+, and K+ than the plowed plots. The infiltration rates of no-tillage plots were higher than those of the plowed plots and, thus, runoff and erosion losses were minimal. Although maximum soil temperatures were higher in the plowed plots, the no-tillage plots had higher soil moisture contents throughout the growing seasons. Greater earthworm activity in the no-tillage plots reduced compaction and crust formation. Yields equal to those from the plowed plots were harvested from the no-tillage plots under suitable crop rotations.